A comprehensive review on various non-isolated power converter topologies for a light-emitting diode driver - Vishnuram, Pradeep; Narayanamoorthi, R.; Vijayakumar, K.; Bajaj, Mohit; Shouran, Mokhtar; Abdul Samad, Bdereddin; Kamel, Salah (Frontiers in Energy Research, 2022)
Light-emitting diode (LED) lighting applications aided by an electronic power control have become very attractive in the recent years. For LED lighting applications, it is essential to design a converter with single/multi-output for handling multiple loads. As the LED load is more sensitive to the change in input/converter parameters, it is necessary to regulate the current concerning the design specifications. In this paper, several LED topologies are reviewed with a focus on power density, single/multi-load operation, size, and reliability. Several converter topologies are reviewed and compared in terms of power rating, number of semiconductor switches, isolation, and efficiency. Various modulation techniques used for dimming control are described in brief. The salient features of each converter topology are discussed with the power rating and application for which the topology can be preferred. So, the selection of the power factor correction (PFC) and low source side harmonics converter topology is presented. This paper will be helpful to the researchers who are working on the development of LED drivers.